Local Wisdom in the Management of Komplangan Mahoni Land: An Ethnoecological Study of the Gubugklakah Village Community - Hulya Urwati (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify the types of cultivated plants planted under mahogany stands in Gubugklakah Village, analyze land management techniques by the community, and examine the forms of utilization of cultivated plants as part of local ecological knowledge. Methodology: This research employed descriptive and quantitative methods through field plotting, plant inventory, direct observation, free and semi-structured interviews, and environmental parameter measurements. The tools used included a GPS, compass, thermometer, pH meter, camera, oven, furnace, and measuring tape. Data analysis was conducted using vegetation analysis, the Importance Value Index (IVI), Use Value Index (UV), literature review, and demographic survey. Main Findings: The research results show that there are 18 cultivated plant species and 15 wild plant species in the mahogany plantation. Land management techniques include terracing, bed construction, intercropping, seasonal planting, watering, and fertilization. Banana and corn have the highest utility value. Community utilization of cultivated plants remains limited, although land management demonstrates ecological adaptation based on local knowledge. Novelty/Originality of this study: The novelty of this research lies in the ethnoecological analysis of cultivated plants in mahogany plantations through the integration of vegetation inventory, land management techniques, and plant utilization values. This research enriches knowledge of community adaptation strategies within local agroforestry systems and provides a scientific basis for the development of sustainable agriculture based on local wisdom.